Pengaruh Pendapatan, Pengetahuan Investasi dan Perilaku Keuangan terhadap Keputusan Investasi : Studi Kasus pada Pegawai Badan Urusan Administrasi Mahkamah Agung Republik Indonesia - Lia Fatma Tsania (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of income, investment knowledge, and financial behavior on investment decisions among Civil Servants at the Administrative Affairs Agency of the Supreme Court of the Republic of Indonesia. A quantitative survey method was employed. Data were collected through an online questionnaire distributed via Google Forms to 170 respondents selected using the simple random sampling technique. The research instrument consisted of 40 statement items measured using a five-point Likert scale. Data were analyzed using IBM SPSS Statistics Version 27, including validity, reliability, classical assumption tests, and multiple linear regression analysis. The results indicate that income, investment knowledge, and financial behavior have a positive and significant effect, both partially and simultaneously, on investment decisions. The Adjusted R Square value of 0.635 indicates that 63.5% of the variation in investment decisions is explained by the three independent variables, while 36.5% is influenced by other factors outside this study.